Piper methysticum altera a atividade locomotora e parâmetros bioquímicos em Drosophila melanogaster - Krum, Bárbara Nunes (2017)
Piper methysticum (P. methysticum), popularly known as Kava Kava, is used for the treatment of anxiety due to its action on the Central Nervous System (CNS). However, its action mechanism continues being investigated. In order to minimize and replace the use of rodents in some experimental models, Drosophila melanogaster (D. melanogaster) is an example of alternative model, used mainly in genetic studies, CNS diseases and the screening of drugs with pharmacological potential. Therefore, the present study investigated the effects of P. methysticum on behavioral and biochemical changes in D. melanogaster. To perform the tests D. melanogaster were exposed to different concentrations of the crude extract of P. methysticum (0.001, 0.01, 0.1, 1 e 10 mg/mL). In the survival curve, there was a significant increase in the number of deaths of D. melanogaster at the concentration of 0.001, 1 and 10 mg/mL. For negative geotaxis test, oxidative stress parameters and tyrosine hydroxylase (TH) immunoreactivity, treatments of 5 or 12 days were performed with the same concentrations of P. methysticum used in the survival curve. Negative geotaxis test, there was a decrease in the locomotor activity of D. melanogaster at concentrations of 1 and 10 mg/mL during 5 days of treatment and a decrease in the concentration of 10 mg/mL during 12 days of treatment with the plant. After this, D. melanogaster were treated with 0.1 mg/mL P. methysticum for 5 or 12 days and then placed in a new treatment medium containing 5 or 500 μM reserpine for 2 days. This association potentiated the reduction in the locomotor activity of D. melanogaste in the two evaluated times, indicating a possible synergism between the two compounds. In the oxidative stress parameters, there was an increase in the levels of protein thiol and reactive oxygen and nitrogen specimens at the concentration of 10 mg/mL only for the treatment of 12 days with the plant. TH immunoreactivity assay, there was an increase in TH concentrations at 0.001 mg/mL and a decrease of TH levels at the 10 mg/mL concentration after 5 days of treatment. After 12 days of treatment there was a decrease in TH levels at concentrations of 1 and 10 mg/ mL of the extract. The data suggest that the decrease of the survival of the D. melanogaster as well as the it locomotor activity could be associated with a decrease of the immunoreactivity of the TH enzyme and consequently a possible involvement of the monoaminergic system. However, further studies should be carried out in order to verify the effects of P. methysticum on D. melanogaster.